Herschel unveils a puzzling uniformity of distant dusty galaxies - Elbaz, D; Hwang, H; Magnelli, B; Daddi, E; Aussel, H; Altieri, B; Amblard, A; Andreani, P; Arumugam, V; Auld, R; Babbedge, T; Berta, S; et al. (2010)
The Herschel Space Observatory enables us to accurately measure the bolometric output of starburst galaxies and active galactic nuclei (AGN) by directly sampling the peak of their far-infrared (IR) emission. Here we examine whether the spectral energy distribution (SED) and dust temperature of galaxies have strongly evolved over the last 80% of the age of the Universe. We discuss possible consequences for the determination of starformation rates (SFR) and any evidence for a major change in their star-formation properties. We use Herschel deep extragalactic surveys from 100 to 500 μ m to compute total IR luminosities in galaxies down to the faintest levels, using PACS and SPIRE in the GOODS-North field (PEP and HerMES key programs). An extension to fainter luminosities is done by stacking images on 24 μ m prior positions. We show that measurements in the SPIRE bands can be used below the statistical confusion limit if information at higher spatial resolution is used, e.g. at 24 μ m, to identify "isolated" galaxies whose flux is not boosted by bright neighbors. Below z ∼ 1.5, mid-IR extrapolations are correct for star-forming galaxies with a dispersion of only 40% (0.15 dex), therefore similar to z ∼ 0 galaxies, over three decades in luminosity below the regime of ultra-luminous IR galaxies (ULIRGs, LIR ≥ 1012 L⊙). This narrow distribution is puzzling when considering the range of physical processes that could have affected the SED of these galaxies. Extrapolations from only one of the 160 μ m, 250 μ m or 350 μ m bands alone tend to overestimate the total IR luminosity. This may be explained by the lack of far-IR constraints around and above ∼150 μ m (rest-frame) before Herschel on those templates. We also note that the dust temperature of luminous IR galaxies (LIRGs, LIR ≥ 1011 L⊙) around z ∼ 1 is mildly colder by 10-15% than their local analogs and up to 20% for ULIRGs at z ∼ 1.6 (using a single modified blackbody-fit to the peak far-IR emission with an emissivity index of β = 1.5). Above z = 1.5, distant galaxies are found to exhibit a substantially larger mid- over far-IR ratio, which could either result from stronger broad emission lines or warm dust continuum heated by a hidden AGN. Two thirds of the AGNs identified in the field with a measured redshift exhibit the same behavior as purely star-forming galaxies. Hence a large fraction of AGNs harbor coeval star formation at very high SFR and in conditions similar to purely star-forming galaxies. © 2010 ESO.